Botswana : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Botswana. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation focuses on Botswana near- and medium-term challenges and policy priorities and was prepared before COVID-19 became a global pandemic and resulted in unprecedented strains in global trade, commodity, and financial markets. Gross domestic product growth is forecasted to pick up to 4.4 percent in 2020 and 5.6 percent in 2021 as the diamond industry recovers somewhat, and a new copper mine comes on stream. Growth will ease back to around 4 percent over the medium term. Risks to the outlook include faster-than-anticipated slowdown in key trading partners, shifts in consumer preferences to synthetic diamonds, and climate shocks. The size and pace of the planned adjustment are consistent with Botswana's fiscal space, but the composition of the adjustment should protect efficient capital and social spending. Furthermore, given that buffers are being eroded, it is critical that consolidation starts as envisaged in FY2020, as it would help start addressing external imbalances and contribute to a gradual rebuilding of buffers over the medium term. In order to strengthen the monetary transmission mechanism and deepen the domestic financial market, there is a need to develop the secondary market for government securities, leverage Fintech, facilitate the attachment of collateral, and improve credit information.